Long-term trends in the world energy market - Jelisavac Sanja (Međunarodni Problemi, 2007)
The author points out that energy reserves are adequate to meet demand till 2030. The principal uncertainty in global energy supply prospects is its price. We expect that international trade in energy, and fossil fuels in particular, will be on the rise. Technological advances and technology breakthroughs could radically alter the long-term picture of energy supply beyond 2006.